An orthotopic glioblastoma animal model suitable for high-throughput screenings. Issue 11 (10th May 2018) - Pudelko, Linda; Edwards, Steven; Balan, Mirela; Nyqvist, Daniel; Al-Saadi, Jonathan; Dittmer, Johannes; Almlöf, Ingrid; Helleday, Thomas; Bräutigam, Lars
Abstract: Background: Glioblastoma (GBM) is an aggressive form of brain cancer with poor prognosis. Although murine animal models have given valuable insights into the GBM disease biology, they cannot be used in high-throughput screens to identify and profile novel therapies. The only vertebrate model suitable for large-scale screens, the zebrafish, has proven to faithfully recapitulate biology and pathology of human malignancies, and clinically relevant orthotopic zebrafish models have been developed. However, currently available GBM orthotopic zebrafish models do not support high-throughput drug discovery screens. Methods: We transplanted both GBM cell lines as well as patient-derived material into zebrafish blastulas. We followed the behavior of the transplants with time-lapse microscopy and real-time in vivo light-sheet microscopy. Results: We found that GBM material transplanted into zebrafish blastomeres robustly migrated into the developing nervous system, establishing an orthotopic intracranial tumor already 24 hours after transplantation. Detailed analysis revealed that our model faithfully recapitulates the human disease. Conclusion: We have developed a robust, fast, and automatable transplantation assay to establish orthotopic GBM tumors in zebrafish. In contrast to currently available orthotopic zebrafish models, our approach does not require technically challenging intracranial transplantation of single embryos. Our improved zebrafish model enables transplantation of thousands of embryos per hour, thus providing an orthotopic vertebrate GBM model for direct application in drug discovery screens.